Synthesis and Characterization of Fe(III), Co(II), Ni(II), Cu(II) and Zn(II) Complexes of Phenyl Amino Acetic Acid Ethyl Acetoacetate-2-ylmethylene Hydrazone - I. Kashar, Tahani; M. El-Nahas, Ahmed; M. El-Mughamsi, Asmaa (Asian Journal of Chemistry, 2010)
Phenyl amino acetic acid ethyl acetoacetate-2-ylmethylene hydrazone and its Mn(II), Fe(III), Co(II), Ni(II), Cu(II) and Zn(II) complexes have been synthesized and characterized by elemental analyses, IR, UV-vis, electrical conductivity, magnetic moment and thermal analyses (DTA, TGA). All the investigated complexes are mononuclear. The ligand behaves as di- or tridentates mono or dibasic acid in mononuclear complexes. Density functional theory (DFT) calculations indicated that the diketo forms are the most tautomers and the agreement between the calculated and experimental frequencies is very good.